A NEW SPECIES OF BEGONIA (BEGONIACEAE) FROM MANUSELA NATIONAL PARK, SERAM - I MADE ARDHAKA; WISNU HANDOYO ARDI; NI KADEK EROSI UNDAHARTA; I. G. TIRTA (Research Center for Biology, 2016)
ARDHAKA, I. M., ARDI, W. H., UNDAHARTA, N. K. E. & TIRTA, I. G. 2016. A new species Begonia from Manusela National Park, Seram. Reinwardtia 15(1): 61 – 64. — A new species of Begonia, B. manuselaensis Ardhaka & Ardi, is described from Seram, Maluku province, Indonesia. The species is endemic to Seram and belongs to Begonia section Petermannia.